2023
DOI: 10.3390/healthcare11111521
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Induction and Caesarean Sections Performed Using the Robson Classification in a University Hospital in Spain from 2010 to 2021

Rafael Vila-Candel,
Nadia Piquer-Martín,
Nerea Perdomo-Ugarte
et al.

Abstract: Background: The Robson Ten Group Classification System (RTGCS) enables the assessment, monitoring, and comparison of caesarean section rates both within healthcare facilities and between them, and the indications of caesarean sections (CS) performed in a maternity ward. The aims of the present study were to conduct an analysis to assess the levels and distribution of birth from a descriptive approach by CS in La Ribera University Hospital (Spain) between 2010–2021 using the Robson classification; to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies suggested that labour induction can negatively affect the emotional well-being of women in the postpartum period [ 40 , 41 ], which is a factor related to the BF duration in the literature [ 42 , 43 ]. Caesarean sections, especially those performed emergently, may be associated with initial difficulties in breastfeeding initiation due to the need for surgical recovery and other potential factors [ 44 ]. Thus, the relationship between labour induction and early BF abandonment may result from a combination of factors related to the birthing experience, potential complications, and the influence on natural hormonal processes that support BF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that labour induction can negatively affect the emotional well-being of women in the postpartum period [ 40 , 41 ], which is a factor related to the BF duration in the literature [ 42 , 43 ]. Caesarean sections, especially those performed emergently, may be associated with initial difficulties in breastfeeding initiation due to the need for surgical recovery and other potential factors [ 44 ]. Thus, the relationship between labour induction and early BF abandonment may result from a combination of factors related to the birthing experience, potential complications, and the influence on natural hormonal processes that support BF.…”
Section: Discussionmentioning
confidence: 99%